Effect of shading on series solar modules: simulation and experimental results - Melício, Rui (2014)
This paper is on the five parameters modeling for photovoltaic systems. Normally, the technical information for photovoltaic panels is too restricted to identify the five parameters. So, an undemanding heuristic method is adopted in this paper, requiring only information on open circuit, maximum power point and short circuit conditions. The I-V and the P-V curves for a series connected monocrystalline photovoltaic system is obtained from the parameters identification using the heuristic method and validated by comparison with experimental curves. Also, a simulation for partial shading on the photovoltaic system is presented to illustrate a feasible assessment during the design of a PV system for loss of energy conversion due to shading.